Prayer : finding the heart's true home - Foster, Richard J. ([San Francisco] : HarperSanFrancisco, 1992)
Best-selling author Richard J. Foster offers a warm, compelling, and sensitive primer on prayer, helping us to understand, experience, and practice it in its many forms - from the simple prayer of beginning again to unceasing prayer. He clarifies the prayer process, answers common misconceptions, and shows the way into prayers of contemplation, healing, blessing, forgiveness, and rest. Coming to prayer is like coming home, Foster says. "Nothing feels more right, more.
like what we are created to be and to do. Yet at the same time we are confronted with great mysteries. Who hasn't struggled with the puzzle of unanswered prayer? Who hasn't wondered how a finite person can commune with the infinite Creator of the universe? Who hasn't questioned whether prayer isn't merely psychological manipulation after all? We do our best, of course, to answer these knotty questions but when all is said and done, there is a sense in which these.
mysteries remain unanswered and unanswerable....At such times we must learn to become comfortable with the mystery." Foster shows how prayer can move us inward into personal transformation, upward toward intimacy with God, and outward to minister to others. He leads us beyond questions to a deeper understanding and practice of prayer, bringing us closer to God, to ourselves, and to our community.
Simple prayer -- Prayer of the forsaken -- The prayer of examen -- The prayer of tears -- The prayer of relinquishment -- Formation prayer -- Covenant prayer -- The prayer of adoration -- The prayer of rest -- Sacramental prayer -- Unceasing prayer -- The prayer of the heart -- Meditative prayer -- Contemplative prayer -- Praying the ordinary -- Petitionary prayer -- Intercessory prayer -- Healing prayer -- The prayer of suffering -- Authoritative prayer -- Radical prayer.
Includes bibliographical references (p. 257-268) and indexes.
Keywords: Prayer -- Christianity